Tropical Mudejar: Mosque-type chapels in Mexico and their role in early Spanish America. - Barragan Castro, Luis Carlos (AUC Knowledge Fountain, 2017)
Mudejar, the architectural style that emerged in Spain during the Reconquista, is relatively common in Spanish Colonial architecture in America, but it was merely an echo of the contemporary buildings constructed in Spain during the years of the colony. The presence of completely Islamic structures, however, such as the Mosque-type chapels, defy that observation, because the hypostyle plan had not been used in Spain for at least a hundred years. This research compares five chapels built in Mexico during the sixteenth century that follow a hypostyle plan, which resemble mosques in almost every aspect. It also proposes that these Mosque-type churches were a creative solution to accommodate the indigenous population, their patterns of worship and their number during the early years of the colony. These Islamic-inspired designs precede the open-air chapels, which became a common feature in sixteenth century Mexican architecture. An additional transcultural element given by the main users and builders of these chapels enrich the panorama of Mudejar art, mixing Native American religion and culture with an already rich Spanish Mudejar taste.